Characteristics of Long-Term Survivors of Epithelial Ovarian Cancer - Cress, Rosemary D. (Obstet Gynecol, 2015)
OBJECTIVE: To identify characteristics associated with long-term survival forepithelial ovarian cancer patients using the California Cancer Registry. METHODS: A descriptive analysis of survival of all California residents diagnosed with epithelial ovarian cancer between 1994 and 2001 was conducted using patients identified through the cancer registry with follow up through 2011. Characteristics of the patients who survived more than 10 years (long-term survivors) were compared to three other cohorts: patients who survived less than 2 years, those who survived at least 2 but no more than 5 years, and those who survived at least 5 but no more than 10 years. RESULTS: A total of 3,582 out of 11,541 (31% CI=30.2%, 31.8%) of the patients survived more than 10 years. Younger age, early stage, low-grade, and non-serous histology were significant predictors of long-term survival, but long-term survivors also included women with high-risk cancer. CONCLUSION: Long-term survival is not unusual in patients with epithelial ovarian cancer, even in those with high-risk disease. Many of the prognostic factors are well known, but it remains to be determined why some patients with advanced stage high-grade cancers survive longer than others with the same histology. These findings are important for patient counseling.